Plant Species Diversity and Community Structure in the Outer Fringes of Kedarnath Wildlife Sanctuary, Western Himalaya: Conservation Implications - Rawat, G. S.; Sathyakumar, S.; Narendra Prasad, S. (Indian Forester, 1999)
Studies on the plant species diversity and community structure were carried in the outer fringes (l550m - 1900m) of Kedarnath Wildlife Sanctuary, Western Himalaya. Five sites were selected along the gradient of human use which represented various stages of Oak-Rhododendron Quercus leucotrichophora - Rhododendron arboreum community. The tree density varied significantly among the sites (ANOVA p<0.001) but there was no significant variation in the shrub density. The diversity of tree and shrub species have been compared separately at various sites using Shannon-Wiener index. The number of woody species was highest in the moderately disturbed site where as lowest in the Oak forest protected and artificially regenerated by the villagers. Moderately disturbed site showed best regeneration of ban Oak. However, maximum tree species diversity, structural (and possibly functional diversity) are exhibited by the old growth forest. Indicators of different seral stages have been identified and conservation implications discussed.